Colorimetry characteristics and color contribution of fluorescence in natural Cr-containing spinel - Jun Tang; Ying Guo; Jun Zhang (Scientific Reports, 2023)
Abstract Fluorescence plays an important role in determining the color appearance of fluorescing minerals. This paper discusses the color mechanism in the red spinel and the color effects from the light source as well as the background on the spinel color. Excitation-Emission Matrices (EEMs) fluorescence spectroscopy was utilized to characterize the fluorescence of natural Cr-doped magnesia-alumina spinel from Myanmar. EMP, LA-ICP-MS, and optical spectroscopy were applied to study the spinel's chemical compositions and color mechanism. X-Rite Ci-7800 spectrophotometer, which is useful to measure colors for fluorescing minerals, was employed to acquire color data of spinel in daylight and incandescent light. The results indicated the higher value of Cr/Fe makes pinkish-red spinel has a much stronger red fluorescence effect than dark-red spinel. The two narrow absorption bands at ~ 25,500 cm−1 (with a broad absorption band at ~ 24,100 cm−1) and ~ 18,570 cm−1 in the optical absorption spectrum are assigned to spin-allowed electronic d-d transitions 4 A 2g  → 4 T 1g (F) and 4 A 2g  → 4 T 2g (F) in Cr3+ at the M site. The EEMs spectra of the pinkish-red spinels show twin emissions at 706 nm excited both by ~ 380 nm and ~ 535 nm radiations, which is the key to the bright neon red color in pinkish-red spinel. The colorimetry study suggests the strong red fluorescence produced by < 460 nm radiation contributes more than 10% lightness and chroma in pinkish-red spinel under daylight. The lightness and the chroma of the spinels grow with the decrease of the background grayscale. The differentiation of spinel colors in dark conditions is lower than that in a bright environment.